2017
DOI: 10.1016/j.ppedcard.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Early extubation in pediatric heart surgery across a spectrum of case complexity: Impact on hospital length of stay and chest tube days

Abstract: Unstructured abstract Early extubation is increasingly common in congenital heart surgery, but there are limited outcomes data across the spectrum of case complexity. We performed a retrospective review of 201 pediatric operations using cardiopulmonary bypass between 2012 and 2014. Patients extubated in the operating room or immediately on arrival to the ICU were compared to those extubated by traditional protocols. In-hospital mortality, major complications, need for re-intubation, hospital length of stay, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…In a previous cardiac surgery study, on-table extubation helped curtail costs and shorten hospital length of stay. [25] In our study, we identified a significant reduction of SICU stay by early extubation. This result was similar to the observation from a previous study by Beamer.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In a previous cardiac surgery study, on-table extubation helped curtail costs and shorten hospital length of stay. [25] In our study, we identified a significant reduction of SICU stay by early extubation. This result was similar to the observation from a previous study by Beamer.…”
Section: Discussionmentioning
confidence: 66%
“…This result was similar to the observation from a previous study by Beamer. [25] In addition, we also noted a decrease in hospitalization costs, but the difference was not significant because of our limited sample size.…”
Section: Discussionmentioning
confidence: 81%
“…3 Hospital LOS and chest tube days were significantly lower for the early extubation group in both the unadjusted and adjusted analyses. 3 The authors' conclusions were early extubation could be performed safely in congenital heart surgery across a spectrum of case complexity. 3 No increased early mortality or reintubation was observed with early extubation, although there were important differences between the groups that merits further study.…”
Section: Effects Of Interventionsmentioning
confidence: 85%
“…3 The authors' conclusions were early extubation could be performed safely in congenital heart surgery across a spectrum of case complexity. 3 No increased early mortality or reintubation was observed with early extubation, although there were important differences between the groups that merits further study. 3 Perioperative and Postoperative Stress Response.…”
Section: Effects Of Interventionsmentioning
confidence: 98%
See 1 more Smart Citation